2015
DOI: 10.1016/j.yexcr.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Intrabody-mediated diverting of HP1β to the cytoplasm induces co-aggregation of H3–H4 histones and lamin-B receptor

Abstract: HighlightsIntrabodies against heterochromatin protein 1 β (HP1β) inhibit its traffic to the nucleus. Anti-HP1β intrabodies sequester HP1β in cytoplasmic aggregates. Anti-HP1β scFv causes co-aggregation of LBR and H3-H4 histones in the cytoplasm. Methylated histone H3 at K9 (Me9H3) is not affected by anti-HP1β scFv expression. Anti-HP1β scFv induces altered nuclear morphology and apoptosis. Diverting a Q2 protein from its intracellular location is a unique property of intrabodies. To interfere with the intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have documented the efficacy of PEST-fusion intrabodies against pathogenic proteins such as huntingtin 46 and α-synuclein 51 . It was also shown that intrabodies can disrupt the subcellular distribution of target proteins, including by inhibition of nuclear−cytoplasmic translocation 52 , 53 . Although cytoplasmic nonaggregated TDP-43 (TDP-43 mNLS ) was not degraded by 3B12A scFv in cultured cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the efficacy of PEST-fusion intrabodies against pathogenic proteins such as huntingtin 46 and α-synuclein 51 . It was also shown that intrabodies can disrupt the subcellular distribution of target proteins, including by inhibition of nuclear−cytoplasmic translocation 52 , 53 . Although cytoplasmic nonaggregated TDP-43 (TDP-43 mNLS ) was not degraded by 3B12A scFv in cultured cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Protein relocation is an approach to interfere with target protein function through trapping it with binder molecule and thereby preventing the target protein transport to a defined cellular compartment. The feasibility of such strategy was demonstrated with intracellular antibodies, which inhibited heterochromatin protein 1β traffic to the nucleus ( Cardinale et al, 2015 ), resulting in altered nuclear morphology and apoptosis. Another group reported intracellular antibody binding to Sec61 and prevention of its transport from the ER toward endosomes ( Zehner et al, 2015 ).…”
Section: Strategies For Intracellular Targeting Of Antibodies Their mentioning
confidence: 99%
“…The generation of the different types of intrabodies also requires very different amounts of effort. Although aggregating intrabodies have also been reported to cause a phenotype [12] , cytosolic intrabodies, ideally i. need to fold correctly in the cytosol in order to be functional and ii. need to bind to a selected epitope in a way allowing neutralization of the target function.…”
Section: Different Types Of Intrabodiesmentioning
confidence: 99%
“…Inhibition of one of the several functions of a target protein can furthermore be achieved by the ability of intrabodies fused to a signal sequence to relocate proteins, as has been demonstrated by the knockdown of Sec61, which was relocated intracellularly by an ER-intrabody to inhibit its function in the endosomes without disrupting its vital function for protein biosynthesis in the ER [53] . Another study reported the re-localization of a target protein to prevent its function in the nucleus [12] . A similar approach allowed to block the pathogenic polymerization of Z α1-antitrypsin while maintaining its antiproteinase activity without which patients would develop a lung disease [37] .…”
Section: Intrabodies For Therapy?mentioning
confidence: 99%